Spatiotemporal variation characteristics of ecosystem carbon storage in Zhengzhou and future multi-scenario simulation prediction - Li, Lei; Li, Fuhao; Li, Qingsong; Ji, Guangxing; Guo, Yulong; Li, Meng; Li, Genming; Chen, Weiqiang (Frontiers in Environmental Science, 2025)
As the typical megacity in the Central Plains, the simulation and prediction of Zhengzhou’s future land use and ecosystem carbon storage are of great significance for regional green and coordinated development. Based on land use data and CMIP6 data, the study simulated land use types from 2030 to 2050 through plus model. Then the InVEST model is used to estimate its ecosystem carbon storage. The results show that: (1) Arable land is the main type of land use in Zhengzhou from 2000 to 2020. During the period, the conversion between land use type is mainly manifested as the conversion of arable land into construction land. The distribution of the built-up area has changed from one center with multiple scattered dots to one center with a radial spider-web-like pattern. (2) In 2050, arable land in the SSP126 scenario is the only one of the three scenarios to decline, but the area of forest land and so on in this scenario is the largest of the three. The area changes trend of each land use type in the two scenarios of SSP245 and SSP585 are relatively consistent. (3) The areas with high ecosystem carbon storage value are mainly distributed in the forest area in the west of the study area. The regional ecosystem carbon storage value of SSP126 scenario in 2050 is the highest, which is 5.7762 × 107t. The ecosystem carbon storage value of SSP585 scenario decreased the most, with a total reduction of 0.6667 × 107t. (4) The spatiotemporal variation of ecosystem carbon storage in Zhengzhou is the result of natural and social factors, among which the average annual temperature is the strongest explanation. This study provides a theoretical basis for the scientific formulation of land use planning in Zhengzhou, as well as the coordinated development of man and nature.